Style of Language in the Kumpulan Puisi Baju Bulan: Seuntai Puisi Pilihan By Joko Pinurbo (Stylistic Study) - Andre Felix Nababan; Parlaungan Ritonga; Emma Marsella (International Journal of Education, Information Technology, and Others, 2026)
This study aims to describe the types of figurative language and the functions of figurative language contained in the buku kumpulan puisi Baju Bulan: Seuntai Puisi Pilihan by Joko Pinurbo through stylistic studies. This study uses a descriptive qualitative approach. The research data are 16 selected poems taken as samples from a total of 82 poems in the collection. The classification of figurative language is based on the theory of Gorys Keraf and Henry Guntur Tarigan, while the analysis of linguistic functions refers to the theory of Roman Jakobson. The results show that there are 85 data covering 20 types of figurative language. The types of figurative language found include personification, metaphor, simile, antithesis, irony, paradox, hyperbole, satire, sarcasm, metonymy, antonomasia, allusion, eroticism, parallelism, euphemism, polysindenton, epizeukis, asyndone, anaphora, and assonance. The most dominant figurative language is metaphor (13 data) and personification (10 data), which shows the poet's tendency to use figurative language to build symbolic and imaginative meanings. From the aspect of the function of language style, 67 data were found divided into six functions: poetic, emotive, referential, conative, metalinguistic, and phatic functions. The poetic function is the most dominant (20 data), confirming that the poems in this collection really emphasize the aesthetic aspect and beauty of language. Overall, the use of language style in Joko Pinurbo's works not only functions as a decoration of the text, but also as a means of conveying social criticism, philosophical reflection, and deep emotional expression